MANAJEMEN MUTU KUALITAS STAFF DAN MUTU STAFF RUMAH SAKIT GAMBIRAN KOTA KEDIRI - Reny Nugraheni; Gerardin Ranind Kirana (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The hospital is a health service institution that provides two types of services to the community, namely first health services and second administrative services. Staff service is a form of professional service which is an integral part of health services based on nursing knowledge and tips aimed at individuals, families, groups or communities, both healthy and sick. The general objective of this study is to analyze how the performance of staff and the quality of staff at Gambiran Hospital. This research uses descriptive research and uses a cross sectional approach. The data collection method used was a questionnaire with 4 rating scales (Lichert). The population that was used as the data source in this study was also used as the research sample, namely male and female staff at Gambiran Hospital, Kediri Regency with a total of 30 nurses. The results of 26 questions from 3 categories indicate that overall staff satisfaction is good. The conclusion of this study is that overall employee satisfaction at Gambiran Hospital in Kediri Regency is good in the categories of work motivation, work management and work environment